Coexistence - Han, HuanHuan (Nanyang Technological University, 2023)
In this project, I am hoping to challenge the limitations and social norms of how we appreciate and view what beauty is in the context of the floristry industry. To achieve this, I embarked on a journey to determine which sort of waste are being generated. Initially, through my floral journey, I have witnessed tonnes of floral wastes in many different settings and occasions. Admittedly, I have played a part in generating these wastes with my own practice as a floristry designer. As a result, my motivation for this project is to ensure that my start-up and I play a meaningful role in creating awareness and repurposing wastes in an impactful manner. With this in mind, I start by researching, collecting data and reclassifying various types of floral wastes. During this process, I discovered the scale of by-products of the flower industry and how they are discarded as waste.